한국 프로야구에서 가중수정OPS를 이용한 득점력 설명 - 김혁주; Hyuk Joo Kim; 김예형; Yea Hyoung Kim (Ŭngyong tʻonggye yŏnʼgu, 2014)
한국 프로야구에서 장타율과 수정된 출루율을 이용하여 팀의 득점력을 설명하기 위한 지표인 수정OPS와 가중수정OPS를 제시하였다. 먼저 현재 사용되고 있는 출루율을 수정한 수정출루율을 정의하였으며, 수정OPS를 수정출루율과 장타율의 합으로, 가중수정OPS를 수정출루율과 장타율의 가중평균으로 정의하였다. 한국 프로야구 원년인 1982년부터 2013년까지의 정규리그 전 경기 자료를 분석한 결과 수정OPS는 기존의 OPS보다 득점력을 더 잘 설명해 줬다. 연도별 비교에서도 전체 32개 시즌 중 25개의 시즌에서 수정OPS가 기존의 OPS보다 득점력을 더 잘 설명했다. 32개 시즌의 자료를 종합한 결과 수정출루율에 60%, 장타율에 40%의 가중값을 주는 가중수정OPS가 팀의 득점력을 가장 잘 설명하는 타격지표인 것으로 밝혀졌다. 이 가중수정OPS는 Kim (2012)에서 제시된 가중OPS보다도 더욱 높은 설명력을 갖는 것으로 밝혀졌다. We suggested an adjusted OPS and weighted adjusted OPS as indices to explain run productivity of teams using the slugging average and adjusted OBP from Korean professional baseball. First, we defined adjusted OBP by modifying currently used OBP. Next, we defined adjusted OPS as the sum of adjusted OBP and slugging average. We also defined weighted adjusted OPS as the weighted average of adjusted OBP and slugging average. Analysis of the data from all games in the regular seasons from 1982~2013 shows that adjusted OPS better explains runs than OPS. For 25 seasons out of 32 seasons, adjusted OPS explains runs better than OPS. Further, weighted adjusted OPS consisting of adjusted OBP (with weight 60%) and slugging average (with weight 40%) gives the best explanation of run productivity. Weighted adjusted OPS has been found to explain run productivity better than weighted OPS proposed in Kim (2012).